Boxes - Susanne Bauer, Martina Schlünder, Maria Rentetzi (Mattering Press, 2020)
A book full of boxes. A box in itself. An unboxing. This book explores boxes in their broadest sense and size. It invites us to step into the field, unravel how and why things are contained and how it might be otherwise. By turning the focus of Science and Technology Studies (STS) to boxing practices, this collation of essays examines boxes as world-making devices. Gathered in the format of a field guide, it offers an introduction to ways of ordering the world, unpacking their boxed-up, largely invisible politics and epistemics. Performatively, pushing against conventional uses of academic books, this volume is about rethinking taken-for-granted formats and infrastructures of scholarly ordering - thinking, writing, reading. It diverges from encyclopedic logics and representative overviews of boxing practices and the architectural organization of monographs and edited volumes through a single, overarching argument. This book asks its users to leave well-trodden paths of linear and comprehensive reading and invites them to read sideways, creating their own orders through associations and relating. Thus, this book is best understood as an intervention, a beginning, an open box, a slim volume that needs expansion and further experiments with ordering by its users.